SAT0246 Characterising the effects of anakinra therapy on functional status of patients with rheumatoid arthritis using methotrexate. (1st June 2001) - Cohen, SB; Woolley, JM; Chan, WW
Abstract : Background: Objectives: To characterise the effects of anakinra on the functional status of subjects with rheumatoid arthritis using methotrexate. Methods: In a large multidose placebo controlled study of anakinra in subjects with rheumatoid arthritis (RA), functional status was evaluated at baseline and after 24 weeks of therapy using the Health Assessment Questionnaire (HAQ). The HAQ includes questions designed to assess functional status as related to dressing and grooming (D&G), arising (ARI), eating (EAT), walking (WLK), hygiene (HYG), reach (RCH), grip (GRP), and activities (ACT). Comparisons between Methotrexate (MTX) alone (n = 74), and anakinra + MTX (n = 131), based on the combined data for the two highest doses (1 mg/kg and 2 mg/kg), were analysed using change in scores from baseline through 24 weeks. Results: Change scores for all eight of the HAQ scales (Table 1 ) were positive, and six were statistically significant. The biggest effects were seen in reach, hygiene, and eating, while walking showed the smallest effect. Furthermore, by the end of the study a greater percentage of subjects on anakinra + MTX reported functionality without any difficulty, as compared to those on MTX alone (data not shown). Conclusion: Subjects receiving at least 1 mg/kg of anakinra showed statistically significant improvements in functional status as measured by the HAQ. Improvements were evident in almost all of the HAQ scales. Anakinra improves functional status across a wide range of domains in subjects with rheumatoid arthritis.